Recent advances in biomarker detection of oral squamous cell carcinoma - Lan Liu; Xiaowu Zhong; Yue Zhong; Lihua Li (Frontiers in Oncology)
Oral squamous cell carcinoma is among the most prevalent tumours of the oral and maxillofacial region. The initial symptoms are typically minor and may remain misdiagnosed until the disease advances, resulting in a significantly reduced five-year survival rate for patients. Early detection is critical, as it can improve five-year survival rates from below 50% to 70–90%. Due to their reduced sensitivity and intrusive nature, conventional screening methods such as serological testing and histopathological biopsies have limitations in their application. In contrast, emerging technologies including single-cell sequencing, spatial transcriptomics, nanopore sequencing, biosensor technology, and artificial intelligence, among other advanced detection methods, are redefining biomarker discovery. Scalability obstacles still exist, including clinical validation gaps, high implementation costs, and analytical complexity. In order to close the gap between invention and equitable implementation, future efforts should focus on multicenter validation of potential biomarkers and cost-effective integration of these technologies. This will ultimately improve patient prognosis and quality of life. This work aims to comprehensively investigate and evaluate the prospective applications and future developmental potential of these technologies while offering an extensive examination of oral squamous cell cancer biomarker research